2016
DOI: 10.3109/15563650.2015.1126286
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review of the effect of intravenous lipid emulsion therapy for non-local anesthetics toxicity

Abstract: Despite the use of ILE for multiple substances in the treatment of patients with poisoning and overdose, the effect of ILE in various non-local anesthetic poisonings is heterogenous, and the quality of evidence remains low to very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 148 publications
0
59
0
2
Order By: Relevance
“…13,14 The main CYP isoforms involved are CYP3A4 for lidocaine and bupivacaine and CYP1A2 for ropivacaine. CYP3A4 is not mature at birth but is partly replaced by CYP3A7.…”
Section: General Comments On the Use Of Las In Childrenmentioning
confidence: 99%
“…13,14 The main CYP isoforms involved are CYP3A4 for lidocaine and bupivacaine and CYP1A2 for ropivacaine. CYP3A4 is not mature at birth but is partly replaced by CYP3A7.…”
Section: General Comments On the Use Of Las In Childrenmentioning
confidence: 99%
“…ILE has been shown to be an effective antidote for intoxication caused by numerous lipophilic agents. The exact mechanism of action remains unknown, however, it is suspected that ILE serves as a “lipid sink” for fat‐soluble compounds, reducing the amount of free drug in circulation, thereby reducing the drug's toxic effects . Other proposed mechanisms include the “change in energy theory,” in which ILE provides enough fatty acid to facilitate myocardial fatty acid utilization, and/or inhibit endothelial nitric oxide synthase which decreases nitric oxide‐induced vasodilation .…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32] A recently published systematic review on the use of ILE in nonlocal anesthetic overdoses found current evidence to be heterogeneous and low quality. 33 Moreover, several publications have demonstrated adverse effects with its use, including interference with laboratory investigations such as the complete blood count (CBC) and electrolytes. [34][35][36][37][38][39][40][41][42][43] Although ILE use is well established in LAST, the effectiveness of ILE for non-LAST poisonings is still unclear.…”
Section: Importancementioning
confidence: 99%